Microbial Biotransformation to Obtain New Antifungals - Bianchini, Luiz F.; Arruda, Maria F. C.; Vieira, Sergio R.; Campelo, Patrícia M. S.; Grégio, Ana M. T.; Rosa, Edvaldo A. R. (Frontiers in Microbiology, 2015)
Antifungal drugs belong to few chemical groups and such low diversity limits the therapeutic choices. The urgent need of innovative options has pushed researchers to search new bioactive molecules. Literature regarding the last 15 years reveals that different research groups have used different approaches to achieve such goal. However, the discovery of molecules with different mechanisms of action still demands considerable time and efforts. This review was conceived to present how Pharmaceutical Biotechnology might contribute to the discovery of molecules with antifungal properties by microbial biotransformation procedures. Authors present some aspects of (1) microbial biotransformation of herbal medicines and food; (2) possibility of major and minor molecular amendments in existing molecules by biocatalysis; (3) methodological improvements in processes involving whole cells and immobilized enzymes; (4) potential of endophytic fungi to produce antimicrobials by bioconversions; and (5) in silico research driving to the improvement of molecules. All these issues belong to a new conception of transformation procedures, so-called “green chemistry”, which aims the highest possible efficiency with reduced production of waste and the smallest environmental impact.